(untitled) (Asian Journal of Plant Biology, 2014)
The bacteria are a large group of unicellular microorganisms. Bacteria are ubiquitous in every habitat on Earth for example growing in soil, radioactive waste, water and as well as in organic matter and the live bodies of plants and animals. They are small cells, found in the environment as either individual cells or aggregated together as clumps. This study was aimed to identify the bacteria from soil sample obtained from Cameron Highlands. Eight samples were inoculated on Nutrient Agar plate. After obtaining pure culture, stock cultures on Nutrient Agar slant and glycerol stock were prepared and the samples were kept in -20ËšC. Next the samples were further studied using microscopic observation. From this technique, seven Gram positive bacteria and one Gram negative bacteria were obtained. The Gram positive rod shaped was analyzed further using the molecular technique 16S rDNA using pA and pH primers. Then the sample proceeds to bulk. PCR product of approximately 1kb in size was obtained. The purity value of the DNA sample obtained was 1.16 A260/280. The sample was sent for sequencing to NHK Bioscience and Macrogreen (Korea). Only one sample showed positive for 16S rDNA fragments which were analyzed using Basic Local Alignment Search Tool (BLAST) for bacterial identification. The data analysis of the sequence shows that the bacterium obtained was Bacillus pumilus strain.